2007
DOI: 10.1109/lmwc.2007.903467
|View full text |Cite
|
Sign up to set email alerts
|

Multiport Measurement Method Using a Two-Port Network Analyzer With Remaining Ports Unterminated

Abstract: A practical multiport measurement method is presented for the precise characterization of an N-port device using a two-port vector network analyzer. Because the 2 unused ports need not be terminated with matched loads, a test fixture can be simplified. Any influence of the reflections from the unterminated ports can be deembedded by port renormalization. The proposed method was verified with a coupled microstrip line structure.Index Terms-Connector and cable, multiport network, port renormalization, -parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…The measurement can be performed on (1,2,3,4), (1,2,5,6), but not on (1,3,5,6), (2,4,6,8) assuming that the inside routing information is known. At each measurement, the four ports of the device under test (DUT) are connected to the VNA, and the remaining four ports are kept open.…”
Section: Model Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…The measurement can be performed on (1,2,3,4), (1,2,5,6), but not on (1,3,5,6), (2,4,6,8) assuming that the inside routing information is known. At each measurement, the four ports of the device under test (DUT) are connected to the VNA, and the remaining four ports are kept open.…”
Section: Model Validationmentioning
confidence: 99%
“…However, to obtain accurate N-port measurement with two-port VNA, certain conditions need to be met at the external terminations [1][2][3][4][5][6]. I. Rolfes found that one needs to know at least one external termination except the ports where the VNA is connected [3], and D.G.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [3][4][5][6] the unused ports are either connected to auxiliary terminations or left free, it implies that each reflection coefficients must be either known or accurately measured. This leads to complicated procedures which are highly dependent on the accuracy of the measurement of these reflection coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, various papers have been published for the characterization of N-ports with a 2-port analyzer [2], [3]. Furthermore, there are publications [4], [5] and [6] that deal with the problems of error-correction and termination. This work is based on N-port scattering parameters provides a model readily to be used in simulation tools compared to mixed mode scattering parameter models [4].…”
Section: Introductionmentioning
confidence: 99%